2020
DOI: 10.1016/j.ygyno.2019.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Fertility-sparing trachelectomy for early-stage cervical cancer: A proposal of an ideal candidate

Abstract: To propose an ideal patient candidate with early-stage cervical cancer for undergoing fertility-sparing trachelectomy.Methods.-This nationwide, multicenter, retrospective study was conducted by the Japan Society of Obstetrics and Gynecology involving women aged <45 years with clinical stage I-II cervical cancer who had planned fertility-sparing trachelectomy and pelvic lymphadenectomy between 2009 and 2013 (n = 393). Ideal candidates were defined to have a tumor size of ≤2 cm, no lymph node metastasis, no deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…Of the 5598 screened articles, 153 met the predefined inclusion criteria and were assessed for their quality ( Figure 1 ) [ 8 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…Of the 5598 screened articles, 153 met the predefined inclusion criteria and were assessed for their quality ( Figure 1 ) [ 8 , 14 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ,…”
Section: Resultsmentioning
confidence: 99%
“…Smith et al developed a new approach in 1997 called ART that is similar to the traditional radical hysterectomy and addresses the drawbacks of VRT [17]. The oncological safety of ART is guaranteed in early-stage cervical cancer, especially in cases with tumors smaller than 2 cm [18,19]. The first total laparoscopic radical trachelectomy was reported in 2002 by Pomel et al [20] and the first robot-assisted laparoscopic procedure in 2008 by Persson et al [21].…”
Section: Discussionmentioning
confidence: 99%
“…Should the presence of LVSI in FIGO 2018 stage-IB1 tumors be an indication of radical trachelectomy as it was advised in Bentivegna’s review in 2016? A recent Japanese [ 24 ] study proposed different models to select patients for fertility-sparing trachelectomy; LVSI was not part of the final model that included the histology (squamous cell carcinoma, adenocarcinoma or adenosquamous carcinoma), tumor size ≤2 cm, nodal metastases and deep stromal invasion. The prospective GOG study [ 25 ] published in 1990 and other more recent studies showed that disease free-survival was worse among patients with LVSI [ 26 , 27 ], in contrast to a review published in 2004 [ 28 ].…”
Section: Conization or Simple Trachelectomy With Pelvic Lymph Node Dissectionmentioning
confidence: 99%